1990
DOI: 10.1111/j.1365-2265.1990.tb00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay May Overestimate Insulin in Non‐insulin‐dependent Diabetics

Abstract: We have compared insulin concentrations measured by radioimmunoassay (RIA) in plasma from 50 fasting non-insulin-dependent diabetics (NIDDM) with those measured by a new monoclonal antibody-based two-site immunoradiometric assay (IRMA) of insulin (which has no significant cross-reaction with proinsulin-like molecules). We find that the RIA measures the sum of the insulin and proinsulin like molecules and that the IRMA insulin concentrations are 38% of those measured by the RIA in those diabetic subjects. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 12 publications
1
55
0
Order By: Relevance
“…This observation has implications for considerations of pathophysiology, for if a variable is regulated by insulin resistance but the measure being employed to assess it is such a poor indicator of insulin resistance, then one might have to postulate other explanations for the associations. Some years ago, it was shown that the standard insulin immunoassays cross-reacted with the biologically less active insulin precursor molecules proinsulin and its split products [32]. This observation, and emerging assays that permitted specific measures of both insulin and these proinsulin-like molecules, led to studies that found that the correlations of concentrations of these molecules were stronger than those for insulin itself [33], despite their having little biological activity.…”
Section: New Members Of the Metabolic Syndrome And Their Pathophysiologymentioning
confidence: 99%
“…This observation has implications for considerations of pathophysiology, for if a variable is regulated by insulin resistance but the measure being employed to assess it is such a poor indicator of insulin resistance, then one might have to postulate other explanations for the associations. Some years ago, it was shown that the standard insulin immunoassays cross-reacted with the biologically less active insulin precursor molecules proinsulin and its split products [32]. This observation, and emerging assays that permitted specific measures of both insulin and these proinsulin-like molecules, led to studies that found that the correlations of concentrations of these molecules were stronger than those for insulin itself [33], despite their having little biological activity.…”
Section: New Members Of the Metabolic Syndrome And Their Pathophysiologymentioning
confidence: 99%
“…The beta cell is also unable to oscillate in concert with the fluctuations in plasma glucose induced by an oscillating glucose 6 S. Kahn: The relative contributions of insulin resistance and beta-cell dysfunction to the pathophysiology infusion [76]. Finally, inefficient proinsulin processing to insulin [77,78,79,80,81,82,83] and a reduction in the release of islet amyloid polypeptide (IAPP), known also as amylin [84,85,86,87], have been observed in established Type 2 diabetes. These alterations in beta-cell function have been observed in Type 2 diabetic subjects, typically following the administration of intravenous stimuli.…”
Section: Beta-cell Dysfunction In Type 2 Diabetesmentioning
confidence: 99%
“…15 Initially this may be masked by excess production of proinsulins. 47 The rise in proinsulin represents increased insulin demand in T2D, causing depletion of mature insulin-rich granules with mobilisation of immature granules rich in proinsulin.…”
Section: Beta-cell Dysfunction In T2dmentioning
confidence: 99%